Legal Protection of Small and Medium Industries in Dealing with Global Challenge - Dora Kusumastuti, Sutoyo dan Y.Djoko Suseno (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Along with the era of globalization, free trade to enter the market of a country ismarked by the entry of goods from abroad and the impact of one of them is tothreaten the local industry. The aims of this research are: (1) to know the legalprotection of small and medium industries in facing global challenges, (2) Gainway of developing the resources of small and medium industries in order to havecompetitiveness in global era. The type of research is normative research, type andsource of data is secondary data and data source using literature study, dataanalysis technique using deduction logic. Conclusions: (1) small and mediumindustry protection policy through RIPIN, KIN and further elaborated in provincialand district government or city level; (2) In order to realize national industrialdevelopment objectives, SME development efforts need to be continuously carriedout through development strategy through : Human Resource Development (HR)Industry; Employment; Utilization of technology, innovation, and creativity.Key Words : Legal Protection, Small Industry, Medium Industry